Effects of Plasticizer Content and Ceramic Addition on Electrochemical Properties of Cross-Linked Polymer Electrolyte. Issue 5 (28th May 2021) - Du, Zhijia; Chen, X. Chelsea; Sahore, Ritu; Wu, Xianyang; Li, Jianlin; Dudney, Nancy J.
Abstract : The development of a safe electrolyte is the key to improving energy density for next generation lithium batteries. In this work, UV-crosslinked poly(ethylene oxide) (PEO) -based polymer and composite electrolytes are systematically investigated on their ionic conductivity, mechanical and electrochemical properties. The polymer electrolytes are plasticized with non-flammable linear short-chain PEO. In the composite electrolytes, a doped lithium aluminum titanium phosphate (LATP) ceramic, LICGC™, is used as the ceramic filler. It is found that the addition of the plasticizer leads to a tradeoff between ion transport and mechanical properties. In contrast, the addition of ceramic fillers improves both the ionic conductivity and mechanical properties. The sample with 20 wt% of LICGC™ shows a conductivity of ∼0.6 mS cm −1 at 50 °C. This sample also demonstrates much longer cycle life than the neat polymer electrolyte in Li platting/stripping test with a capacity of 1 mAh cm −2 . A full cell made with this composite electrolyte against Li metal anode and high voltage LiNi0.6 Mn0.2 Co0.2 O2 cathode shows 94% capacity retention after 30 cycles, compared to 58% capacity retention with the neat polymer electrolyte. These results demonstrate that a hybrid of polymer/ceramic/non-flammable plasticizer is a promising path to high energy density, high voltage lithium batteries.